Association between iron deficiency anemia and the risk of new-onset tuberculosis infection: a matched cohort analysis - Chen, I-Wen; Chang, Li-Chen; Chang, Ying-Jen; Lai, Yi-Chen; Hung, Kuo-Chuan (Frontiers in Nutrition, 2026)
BackgroundTuberculosis remains a major global health challenge, with emerging evidence suggesting that micronutrient deficiencies may contribute to susceptibility to infection through impaired immune function. Iron deficiency anemia (IDA) is the most common nutritional deficiency worldwide; however, its association with tuberculosis risk remains inadequately characterized across diverse populations. We examined the relationship between IDA and incident tuberculosis in a large multinational cohort.MethodsThis retrospective matched cohort study used data from the TriNetX Research Network spanning 140 healthcare organizations across multiple countries between 2010 and 2020. We identified 177,846 adult patients with IDA and 309,662 controls with dermatitis. After one-to-one propensity score matching, each cohort comprised 160,928 patients. Primary outcomes included incident tuberculosis during 5-year and extended follow-up periods (5–10 years). We incorporated pneumonia and reactive thrombocytosis as positive control outcomes and performed subgroup analyses stratified by sex and age.ResultsIDA was associated with increased tuberculosis risk during 5-year follow-up (hazard ratio [HR] 1.48, 95% confidence interval 1.10–2.00, p = 0.010), with attenuation during extended follow-up. The positive control outcomes demonstrated the expected robust associations with IDA, supporting internal validity. Subgroup analyses revealed numerically stronger associations in male patients (HR 2.06 versus 1.27 in females) and younger adults aged 18–50 years (HR 2.42 versus 1.47 in older individuals), although the interaction terms did not reach statistical significance (p = 0.193 and p = 0.268, respectively), suggesting no significant effect modification. Multivariate analysis revealed differential associations by tuberculosis subtype, with extrapulmonary tuberculosis demonstrating a more pronounced relationship (HR 3.01) than pulmonary disease (HR 1.71).ConclusionIDA demonstrated a significant association with increased tuberculosis risk in this multinational cohort, particularly during early follow-up and for extrapulmonary manifestations. These findings suggest that IDA may represent an underrecognized modifiable risk factor for tuberculosis. Future research is warranted to validate these findings, with particular attention to the potential modifying effect of iron supplementation on tuberculosis risk.